Katie's Cabbage - Stagliano, Katie (Book collections on Project MUSE., 2014)
Katie's Cabbage is the inspirational true story of how Katie Stagliano, a third grader from Summerville, SC, grew a forty-pound cabbage in her backyard and donated it to help feed 275 people at a local soup kitchen. In her own words, Katie shares the story of the little cabbage seedling and the big ideas of generosity and service that motivated her to turn this experience into Katie's Krops, a national youth movement aimed at ending hunger one vegetable garden at a time. Katie's Cabbage reminds us of how small things can grow and thrive when nurtured with tender loving and care and of how one person, with the support of family, friends and community, can help make a powerful difference in the lives of so many. Katie's Cabbage was illustrated by Karen Heid, associate professor of art education at the University of South Carolina School of Visual Art and Design. Editorial assistance was provided by Michelle H. Martin, a dedicated gardener and the Augusta Baker Chair in Childhood Literacy at the University of South Carolina School of Library and Information Science. Patricia Moore-Pastides, First Lady of the University of South Carolina and author of Greek Revival From the Garden: Growing and Cooking for Life, offers a foreword about her friendship with Katie and her admiration of Katie's dream to end hunger one garden at a time.